2009
DOI: 10.1172/jci38151
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2Cm is a critical regulator of branched-chain amino acid catabolism in mice and cultured cells

Abstract: The branched-chain amino acids (BCAA) are essential amino acids required for protein homeostasis, energy balance, and nutrient signaling. In individuals with deficiencies in BCAA, these amino acids can be preserved through inhibition of the branched-chain-α-ketoacid dehydrogenase (BCKD) complex, the rate-limiting step in their metabolism. BCKD is inhibited by phosphorylation of its E1α subunit at Ser293, which is catalyzed by BCKD kinase. During BCAA excess, phosphorylated Ser293 (pSer293) becomes dephosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
199
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(209 citation statements)
references
References 39 publications
7
199
1
2
Order By: Relevance
“…1, A and B). These results confirmed the original report from our previous study on tissue-specific distribution of the PP2Cm mRNA (25) and demonstrated that the LacZ expression faithfully reflected the endogenous PP2Cm expression pattern. A similar pattern of tissue distribution for PP2Cm was also observed at protein level by immunoblotting (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…1, A and B). These results confirmed the original report from our previous study on tissue-specific distribution of the PP2Cm mRNA (25) and demonstrated that the LacZ expression faithfully reflected the endogenous PP2Cm expression pattern. A similar pattern of tissue distribution for PP2Cm was also observed at protein level by immunoblotting (Fig.…”
Section: Resultssupporting
confidence: 90%
“…PP2Cm Expression during Development-PP2Cm expression is critical for normal fish development (27) although PP2Cm-deficient mice can develop to term (25). To evaluate the potential role of BCAA catabolic regulation during early development, we examined the LacZ expression at different stages of development in the PP2Cm knock-out mouse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because BDK requires the E2 core for the bulk of kinase activity (11), abrogating BDK binding to LBD from the E2 core will deactivate the kinase. In support of this mechanism, the presence of KIC in HEK293T cells (13,37) or the dietary supplementation of BCAA in type 2 diabetes rat models (38) promotes the dissociation of BDK from the E2 core, resulting in the dephosphorylation of BCKDC.…”
Section: Discussionmentioning
confidence: 96%